Fotogrammetria da UAV negli interventi di recupero: dalla fase pre-progettuale al cantiere - Donatella Dominici (mediaGEO soc. coop., 2018)
The UAV photogrammetry has a lot of potential in terms of building rehabilitation and post-earthquake reconstruction, of which today there are few references on the international scene. For this reason the authors have elaborated a research aimed to merge the geomatics techniques and the building recovery, arising the develop of a lot of projects. In particular, different scenarios will be presented in the paper, from the pre-design step in the field of sustainable rehabilitation to the optimization of the "construction sites” management.